CARP Institutional Assessment in a Post-2008 Transition Scenario: Implications for Land Administration and Management (LAM) - Felino Cortez; Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2008)
The objective of this paper is to present the land administration and management (LAM) issues on CARP and determine the necessary institutional reforms on LAM in view of CARP expiration in 2008. The paper discussed the adverse effects brought about by weak land policy and poor land administration on attaining the objectives of CARP. The poor land records, the lack of information sharing among government land agencies, the tedious land titling and registration process, the unclear land policies have resulted not only in prolonged implementation of the program but also flawed land redistribution and incomplete transfers of property rights. These outcomes evolved second-generation issues as unperfected titles are traded despite the restrictions imposed by the land reform law. The current LAM in the country showed that the system cannot handle the land transactions that evolve and continue to evolve from hundreds and thousands of transactions involving CARP-awarded lands. There is a need to restore not only the confidence on Torrens system of titling on agriculture lands but also to restore the functioning of the rural land market. This is a key challenge on LAM since it would require reconciling information from key land agencies and including that of the LandBank. It will also require legislative actions on land market regulations, land use policy, and land administration in the country.
Keywords: 330; land reform; land; land ownership and tenure; Bodenreform; Landwirtschaftliche Immobilien; Strukturwandel; Landwirtschaftliche Entwicklung; Philippinen